Accelerated progression of IDH mutant glioma after first recurrence. Issue 5 (22nd January 2019) - Miller, Julie J; Loebel, Franziska; Juratli, Tareq A; Tummala, Shilpa S; Williams, Erik A; Batchelor, Tracy T; Arrillaga-Romany, Isabel; Cahill, Daniel P
Abstract: Background: Isocitrate dehydrogenase (IDH) mutant gliomas are a distinct subtype, reflected in the World Health Organization (WHO) 2016 revised diagnostic criteria. To inform IDH-targeting trial design, we sought to characterize outcomes exclusively within IDH mutant gliomas. Methods: We retrospectively analyzed 275 IDH mutant glioma patients treated at our institution. Progression was determined using low-grade glioma criteria from Response Assessment in Neuro-Oncology. We calculated survival statistics with the Kaplan–Meier method, and survival proportions were correlated with molecular, histologic, and clinical factors. Results: During a median follow-up of 6.4 years, 44 deaths (7.6%) and 149 first progression (PFS1) events (54.1%) were observed. Median PFS1 was 5.7 years (95% CI: 4.7–6.4) and OS was 18.7 years (95% CI: 12.2 y—not reached). Consistent with prior studies, we observed an association of grade, molecular diagnosis, and treatment with PFS1. Following the first progressive episode, 79 second progression events occurred during a median follow-up period of 4.1 years. Median PFS following an initial progressive event (PFS2) was accelerated at 3.1 years (95% CI: 2.1–4.1). PFS2 was a surrogate prognostic marker, identifying patients with poorer overall survival. Conclusion: We report outcomes in a large cohort of IDH mutant glioma, providing a well-characterized historical control population for future clinical trial design. Notably, the interval between first and second recurrence (PFS2, 3.0 y) is shorter than time from diagnosis to first recurrence (PFS1, 5.7 y), evidence that these tumors clinically degenerate from an indolent course to an accelerated malignant phase. Thus, PFS2 represents a relevant outcome for trials investigating drug efficacy at recurrence.